From conquest to coexistenc e ideology and antiquarian intent in the historiography of Israel's settlement in Canaan - Bekkum, K. van. (Culture and History of the Ancient Near East, 2011)
Current research on ancient historiography concentrates on the relation between history and ideology, while the archaeology of the Southern Levant is more and more viewed as a discipline of its own. What happens when these new directions are applied to the historiography of Israel's settlement in Canaan? This study offers a fresh analysis of scholarly debate, a synchronic and diachronic reading of Joshua 9:1-13:7, and a critical evaluation of all the relevant archaeological evidence. This leads to a new historical picture of the Late Bronze - Iron Age transition in the Cisjordanian Southern Levant and to the fascinating conclusion that it was the ideology of the Israelite scribes reworking this episode that instigated them to explore their antiquarian intent.